Photochemical strategies for the green synthesis of ultrathin Au nanosheets using photoinduced free radical generation and their catalytic properties. Issue 39 (2nd October 2018) - He, Suisui; Hai, Jun; Li, Tianrong; Liu, Sha; Chen, Fengjuan; Wang, Baodui
Abstract : A photochemical strategy using photoinduced methylene blue radicals for the green synthesis of ultrathin Au nanosheets. The resulting Au nanosheets show highly sensitive recognition of cancer cells and efficient activity and selectivity toward the hydrogenation of α, β-unsaturated aldehydes. Abstract : Two-dimensional gold nanosheets represent a class of materials with excellent chemical and structural properties, which are often prepared using a template or toxic CO in organic solvents. Here, we report methylene blue (MB) radicals as a reducing agent to grow freestanding hexagonal ultrathin Au nanosheets with well-tuned thicknesses in water. This is the first time that carbon organic radicals have been used as a reducing agent in metal nanosheet synthesis. Notably, no template is used throughout the synthesis process, and the yield of Au nanosheets is very high. It is found that MB is decisive in the growth of Au nanosheets because no Au nanosheets are obtained in the absence of MB with the same reaction parameters. The resulting nanosheets exhibit excellent catalytic activity during H2 O2 decomposition to generate nontoxic O2 . Thus, folic acid-conjugated oxygen generating nanosheets could detect cancer cells in serum samples with high sensitivity through pressure signals. Furthermore, the nanosheets exhibit highly efficient activity and selectivity toward the hydrogenation of α, β-unsaturated aldehydes. We anticipate that using MB radicals for the high-yield synthesis of 2D materials in this unique system has demonstrated their effectiveness and provides a green alternative route for producing other 2D nanomaterials.